Laser-Induced Control of the Optical Response of Aluminum Phthalocyanine Chloride Complexes Dissolved in Ethanol - da Costa Castanheira, Carina; Persch, Andreas; Birk, Paul; Ott, Christian; Pfeifer, Thomas (Frontiers in Physics, 2021)
We show that absorption spectra of aluminum chloride phthalocyanine (AlClPc) in the liquid phase can be dynamically modified through the time-resolved interaction with a second laser pulse during a time window on the order of 100 fs. The observed effects can be explained by laser-induced coherent coupling dynamics between the ground state and a bath of excited states as reproduced by a few-level toy model. The presented results help to understand how intense laser fields interact with complex molecules in solution, but in their laser-controlled response still much alike isolated atoms in the gas phase. This understanding can, in the future, be used to modify and control the dynamics in complex systems.